Gestão da diversidade sob a perspectiva do teto de vidro na PGFN - Silva, Andreza Viana Costa e (2020)
Purpose - The present research aims to investigate the existence of the glass ceiling phenomenon, known in the literature for representing the invisible barriers imposed on women to reach the high institutional hierarchy, at the Procuradoria-Geral da Fazenda Nacional – PGFN. It also intends to understand the ways that phenomenon occurs and identify and analyze the challenges faced by female members of the institution. Methodology – A qualitative research was carried out, with the realization of interviews with women members of the PGFN staff, through a semi-structured script and subsequent content analysis, based on categorization and enumeration criteria, in order to consolidate the information obtained. It was also adopted, in a secondary way, the analysis of data extracted from the Sistema Integrado de Administração de Pessoal - SIAPE human resources system, as well as results of the PGFN Perception Survey, carried out in March 2020, at an institutional level. Findings - It was verified that, although the institution's high hierarchy is composed of men and women, in a considerable numerical balance, the glass ceiling phenomenon can be perceived in the headships of the general coordinations and decentralized units of the PGFN. It was also identified that the female under-representation in the highest positions of the institution is a main result from the dense responsibilities conventionally attributed to the woman in her personal life, being the corollaries of motherhood the hegemonic obstacles to the female professional ascension. Research limitations – The main limitation refers to geographic delimitation as to qualitative research, that was carried out by a professionals with experience in Brasília- DF. Practical implications - By revealing that the PGFN is no exception to the glass ceiling rule and is affected by gender inequality, the contributions of the present study focus on providing data that can assist in the development of inclusive programs in its scope, on the basis of future directions and raising the awareness of its members beyond the professional environment. Social contributions – The results found can be used for the process of social inclusion in the other organs of the Federal Public Administration. Originality – The present study consists of the first gender-specific research carried out within the scope of the PGFN, with grouping of data and perceptions.